Adsorptive Distillation Using Molecular Sieves and Low-Cost Biobased Adsorbents for the Break-up of the Isopropanol–Water Azeotrope - Fawzi Banat; Sameer Al-Asheh; Nasir Al-Lagtah (Adsorption Science & Technology)
The separation of isopropanol from aqueous vapours near the azeotropic composition was investigated using fixed beds packed with type A molecular sieves and biobased adsorbents. Natural palm stones, oak and corncobs were used as new biobased adsorbents. It was possible to break the azeotrope up using any of the afore-mentioned adsorbents. However, in terms of the breakthrough time and the purity of isopropanol in the condensate, the 3 Å molecular sieve was the best followed by 4 Å, palm stones, natural corncobs, natural oak and 5 Å molecular sieves. Activated carbons prepared from the biobased adsorbents showed a lower performance than their natural precursors.